Impact of the time interval between primary or interval surgery and adjuvant chemotherapy in ovarian cancer patients - Farolfi, Alberto; Petracci, Elisabetta; Gurioli, Giorgia; Tedaldi, Gianluca; Casanova, Claudia; Arcangeli, Valentina; Amadori, Andrea; Rosati, Marta; Stefanetti, Marco; Burgio, Salvatore Luca; Cursano, Maria Concetta; Lolli, Cristian; et al. (Frontiers in Oncology, 2023)
Primary debulking surgery (PDS) or interval debulking surgery (IDS) and a platinum-based chemotherapy are the current standard treatments for advanced ovarian cancer (OC). Time to initiation of adjuvant chemotherapy (TTC) could influence patient outcome. We conductedIn a multicenter ret-rospective cohort study of advanced (FIGO stage III or IV) OC treated between 2014-2018 to assess progression-free and overall survival (PFS, OS) in relation with TTC., All patients underwent a germline multi-gene panel for BRCA1/2 evaluation evaluation between 2014-2018. TTC was assessed in relation to progres-sion-free or overall survival (PFS, OS). All analyses were performed for PDS and IDS, separately. Among the 83 patients who underwent PDS, a TTC≥60 days was associated with a shorter PFS (HR 2.02, 95% CI 1.04-3.93, p=0.038), although this association lost statistical significance when adjusted for residual disease (HR 1.52, 95% CI 0.75-3.06, p=0.244 for TTC and HR 2.73, 95% CI 1.50-4.96, p= 0.001 for residual disease). Among 52 IDS patients we This is a provisional file, not the final typeset article found no evidence of asso-ciation between TTC and clinical outcomes. Ascites, type of chemotherapy or germline BRCA1/2 mutational status did not influenced TTC and were not associated with clinical outcome nor in PDS nor in IDS patients.Median TTC was 45 days (1st-3rd quartile: 38-58 days) and 21.9% of patients had a TTC≥60 days. BRCA1/2 mutant patients were 18.3%. Median follow-up time was 67.9 months (95% CI: 56.6-87.8). At univariate analysis, TTC≥60 days was associated with a shorter PFS in 83 PDS pa-tients (HR 2.02, 95% CI 1.04-3.93, p=0.038), although this association lost statistical significance when adjusted for residual disease (HR 1.52, 95% CI 0.75-3.06, p=0.244 for TTC and HR 2.73, 95% CI 1.50-4.96, p= 0.001 for residual disease). Among 52 IDS patients we found no evidence of asso-ciation between TTC and clinical outcomes. In conclusion, longer TTC seems to negatively affect prognosis in patients undergoing PDS, especially those with residual disease.